Evolution of Harvesting Strategies: Replicator and Resource Dynamics - Joelle Noailly; Jeroen van den Bergh; Cees Withagen (Tinbergen Institute, 2001)
Economic theories of managing renewable resources, such as fisheries and forestry, traditionally assume that individual harvesters are perfectly rational and thus able to compute the harvesting strategy that maximizes their discounted profits. The current paper presents an alternative approach based on bounded rationality and evolutionary mechanisms. It is assumed that individual harvesters face a choice between two harvesting strategies. The evolution of the distribution of strategies in the population is modeled through a replicator dynamics equation. The latter captures the idea that strategies yielding above average profits are demanded more than strategies yielding below average profits, so that the first type ends up accounting for a larger part in the population. From a mathematical perspective, the combination of resource and evolutionary processes leads to complex dynamics. The paper presents the existence and stability conditions for each steady-state of the system and analyzes dynamic paths to the equilibrium. In addition, effects of changes in prices are analyzed. A main result of the paper is that under certain conditions both strategies can survive in the long-run.
Keywords: B25; Q30; 330; Evolutionary Economics - Renewable Resources - Common-Property Resource - Fishery; Erneuerbare Ressourcen; Dynamisches Modell; Evolutionsökonomik; Theorie